THE IDEOLOGY OF GENDER DIFFERENCES IN INDONESIAN CULTURE - Betsyeba Desi Wulandari; Indah Arvianti (Jurnal CULTURE (Culture, Language, and Literature Review), 2017)
Gender differences become big problems which are still discussed by many intellectual circles. These differences exist in many life aspects such as culture, economic area, language, and art. Indonesian culture believes that woman and man have different roles. Woman has lower position than man. It is shown from many songs which contain theideology of woman’s inferiority in the society. To establish the relation between song lyrics and ideology of gender differences, critical discourse analysis is applied to identify song writer’s ideology about woman. As the result, there are four ideologies which humiliate woman’s position. It identifies woman as second part in every life aspect which means woman has lower position than man.Keywords: gender differences, critical discourse analysis, ideology, song lyric